ddPCR Quantasoft Files for quantification of Atlantic salmon - Deconinck, Dumas; Hostens, Kris; Taverniers, Isabel; Volckaert, Filip A.M.; Robbens, Johan; Derycke, Sofie (Zenodo, 2021)
Quantasoft data used for the results section in the paper: "Identification and semi-quantification of Atlantic salmon in processed and mixed seafood products using Droplet Digital PCR (ddPCR)" : Identification and semi-quantification of Atlantic salmon in processed and mixed seafood products using Droplet Digital PCR (ddPCR)